The living supply chain : the evolving imperative of operating in real time - Handfield, Robert B.; Linton, Tom (Thomas K.) (Hoboken, New Jersey : Wiley, 2017)
Creates a managerial compass for entering into the LIVING (Live, Intelligent, Velocity, Interactive, Networked, and Good) era of supply chain management and defines the imperative for creating Velocity and Visibility as the focal point for exploiting new digital, mobile, and cloud-based technologiesFrank Crespo, Vice President, Global Supply Network Division (CPO/LogisticsoT Analytics), Caterpillar Inc. Paul Massih, Vice President, BP PSCMYossi Sheffi, Professor, MIT Center for Transportation and LogisticsHau Lee, Professor, Stanford UniversityTim Cummins, CEO, International Association of Commercial and Contract ManagementTom Choi, Harold E. Fear on Eminent Scholar Chair of Purchasing Management, Arizona State University, Executive Director, CAPS ResearchWayne Rothman, Vice President, Enterprise Supply Chain Planning, Johnson & JohnsonJoanne E. Wright, Vice President, IBM Supply Chain.
Introduction -- The living supply chain -- Live!: transparency as a core operating value -- Interactive!: the emergence of federated supply chain networks -- Velocity!: working capital: the overlooked asset -- Intelligent!: linking the genomes of products in your supply chain -- Networked!: co-evolution and co-innovation in federated supply chains -- Good!: the ability to build balanced supply chains -- The future of supply chains.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Industrial procurement -- Management; Business logistics -- Management; Materials management; Gestion de l'approvisionnement.; Logistique (Organisation) -- Gestion; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business logistics -- Management; Industrial procurement -- Management